2002
DOI: 10.1007/s00232-002-1023-7
|View full text |Cite
|
Sign up to set email alerts
|

The Organic Cation Transporters rOCT1 and hOCT2 Are Inhibited by cGMP

Abstract: The electrogenic cation transporters OCT1 and OCT2 in the basolateral membrane of renal proximal tubules mediate the first step during secretion of organic cations. Previously we demonstrated stimulation and change of selectivity for rat OCT1 (rOCT1) by protein kinase C. Here we investigated the effect of cGMP on cation transport by rOCT1 or human OCT2 (hOCT2) after expression in human embryonic kidney cells (HEK293) or oocytes of Xenopus laevis. In HEK293 cells, uptake was measured by microfluorimetry using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…cGMP has been implicated in the regulation of other transport processes in the kidney, although not directly linked to NO production or to PKC stimulation. For example, Hirsch et al (8 -10) described that cGMP is involved in the regulation of Ca 2ϩ and K ϩ channels in a human proximal tubule cell line, whereas others (28) showed that cGMP is involved in the regulation of the organic cation transporters, rOCT1 and hOCT2. cGMP has also been found to be involved in the regulation of vascular tone in which the ET B receptor is included.…”
Section: Discussionmentioning
confidence: 99%
“…cGMP has been implicated in the regulation of other transport processes in the kidney, although not directly linked to NO production or to PKC stimulation. For example, Hirsch et al (8 -10) described that cGMP is involved in the regulation of Ca 2ϩ and K ϩ channels in a human proximal tubule cell line, whereas others (28) showed that cGMP is involved in the regulation of the organic cation transporters, rOCT1 and hOCT2. cGMP has also been found to be involved in the regulation of vascular tone in which the ET B receptor is included.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the role of OCTs in gentamicin uptake, HEK293 cells transfected with OCT1, OCT2, or OCT3 were coincubated for 2 min (linear range) with 1 M ASP ϩ (known OCT substrate) in the presence or absence of nonlabeled gentamicin at an extracellular concentration of 10 mM (30). Figure 3A shows that nonlabeled gentamicin reduced OCT2-mediated influx of ASP ϩ by approximately 50% (89.6 Ϯ 17.5 versus 42.8 Ϯ 10.6 pmol/mg of protein; P ϭ 0.02).…”
Section: Oct2 Transports [ 3 H]gentamicinmentioning
confidence: 99%
“…Pharmacogenetic analysis of the SLC22A7 and pharmacokinetic analysis of its gene products suggest that it plays a role in mediating the balance of intra/extracellular cGMP and consequently regulates this second-messenger signaling pathway (Cropp et al, 2008). In addition, cGMP can serve as an intracellular substrate modulating the expression/activities of other organic ion transporters of the SLC22 family (Schlatter et al, 2002). This cross-talk between different SLC transporters through a transported signaling molecule remains to be explored.…”
Section: Interaction Of Slc and Abc Transporters With Other Signalingmentioning
confidence: 99%